2014
DOI: 10.4149/gpb_2014005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial abilities are not related to testosterone levels and variation in the androgen receptor in healthy young men

Abstract: Abstract. Androgens modulate brain functions such as cognition, emotions and ability. Several studies have shown a correlation between testosterone levels and mental rotation. The aim of the present study was to confirm the influence of salivary testosterone levels, 2D/4D ratio (such as a putative marker of prenatal testosterone), and sensitivity of androgen receptor on the mental rotation in healthy young men. Seventy-five healthy young men (age, 21.86 year) volunteered in this study. Mental rotation scores o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The previous eight studies indicated that testosterone levels are negatively correlated with 2D:4D (Crewther & Cook, ; Durdiaková et al, ; García‐Cruz et al, ; Klimek, Galbarczyk, Nenko, Alvarado, & Jasienska, ; Manning et al, ; Muller et al, ; Perciavalle et al, ; Tan, ), while other two studies showed that they have a strong positive relationship (Chen, Decety, Huang, Chen, & Cheng, ; Durdiaková et al, , ; Oświecimska et al, ). Interestingly, a significant relationship was not found referring to the other 32 studies (Almasry, Domiaty, Algaidi, Elbastawisy, & Safwat, ; Bang et al, ; Benderlioglu & Nelson, ; Borniger, Chaudhry, & Muehlenbein, ; Borráz‐León, Cerda‐Molina, Choi, & Mayagoitia‐Novales, ; Campbell et al, ; Coco et al, ; Durdiaková et al, ; Falter, Arroyo, & Davis, ; Flegr, Lindova, Pivonkova, & Havlicek, ; Folland et al, ; Georgiev, Ryan, Gettler, McDade, & Kuzawa, ; Hönekopp et al, ; Kallai et al, ; Kempel et al, ; Kilduff et al, ; Kubranska et al, ; Li et al, ; Lujan, Bloski, Chizen, Lehotay, & Pierson, ; Maestripieri, Baran, Sapienza, & Zingales, ; Manning et al, ; McIntyre, Li, Chapman, Lipson, & Ellison, ; Neave, Laing, Fink, & Manning, ; Oh, Kim, Yoon, Kim, & Kim, ; Portnoy et al, ; Richards, Klimek, Jasienska, & Marcinkowska, ; Roney & Maestripieri, ; Unal, Urun Unal, Balevi, Tol, & Uyar, ; Vermeersch, T'Sjoen, Kaufman, & Vincke, ; Whitehouse et al, ; Yang, Gray, Zhang, & Pope, ; Zhang et al, ). Regarding our replication study, the results indicate that there is no a significant association between them.…”
Section: Study 2: the Relationship Between Current Testosterone Levelmentioning
confidence: 85%
See 2 more Smart Citations
“…The previous eight studies indicated that testosterone levels are negatively correlated with 2D:4D (Crewther & Cook, ; Durdiaková et al, ; García‐Cruz et al, ; Klimek, Galbarczyk, Nenko, Alvarado, & Jasienska, ; Manning et al, ; Muller et al, ; Perciavalle et al, ; Tan, ), while other two studies showed that they have a strong positive relationship (Chen, Decety, Huang, Chen, & Cheng, ; Durdiaková et al, , ; Oświecimska et al, ). Interestingly, a significant relationship was not found referring to the other 32 studies (Almasry, Domiaty, Algaidi, Elbastawisy, & Safwat, ; Bang et al, ; Benderlioglu & Nelson, ; Borniger, Chaudhry, & Muehlenbein, ; Borráz‐León, Cerda‐Molina, Choi, & Mayagoitia‐Novales, ; Campbell et al, ; Coco et al, ; Durdiaková et al, ; Falter, Arroyo, & Davis, ; Flegr, Lindova, Pivonkova, & Havlicek, ; Folland et al, ; Georgiev, Ryan, Gettler, McDade, & Kuzawa, ; Hönekopp et al, ; Kallai et al, ; Kempel et al, ; Kilduff et al, ; Kubranska et al, ; Li et al, ; Lujan, Bloski, Chizen, Lehotay, & Pierson, ; Maestripieri, Baran, Sapienza, & Zingales, ; Manning et al, ; McIntyre, Li, Chapman, Lipson, & Ellison, ; Neave, Laing, Fink, & Manning, ; Oh, Kim, Yoon, Kim, & Kim, ; Portnoy et al, ; Richards, Klimek, Jasienska, & Marcinkowska, ; Roney & Maestripieri, ; Unal, Urun Unal, Balevi, Tol, & Uyar, ; Vermeersch, T'Sjoen, Kaufman, & Vincke, ; Whitehouse et al, ; Yang, Gray, Zhang, & Pope, ; Zhang et al, ). Regarding our replication study, the results indicate that there is no a significant association between them.…”
Section: Study 2: the Relationship Between Current Testosterone Levelmentioning
confidence: 85%
“…Relationship between the length of AR (CAG)n and current testosterone levels is somewhat inconsistent referring to the previous studies in males: The four studies indicate that the length is positively correlated with the levels (De Naeyer et al, ; Ma et al, ; Manuck et al, ; Stanworth, Kapoor, Channer, & Jones, ); another study, however, demonstrates a significant negative correlation between them (Mosaad, Shahin, Elkholy, Mosbah, & Badawy, ); and another 15 studies report there is no a significant correlation between them at all (Aluja et al, ; Durdiaková et al, ; Durdiaková et al, ; Eisenegger, Kumsta, Naef, Gromoll, & Heinrichs, ; Gettler et al, ; Goutou, Sakka, Stakias, Stefanidis, & Koukoulis, ; Hampson & Sankar, ; Kubranska et al, ; Lapauw, Goemaere, Crabbe, Kaufman, & Ruige, ; Nowak, Diamond, Land, & Moffat, ; Ryan et al, ; Sankar & Hampson, ; Schneider et al, ; Schneider, Zitzmann, Gromoll, Ladwig, & Berger, ; Stiger et al, ). Regarding the same relationship analyzed by previous studies for females, two studies indicate the length is positively correlated with the levels (Peng et al, ; Skrgatic, Baldani, Cerne, Ferk, & Gersak, ); such relationship, however, is significantly negative (Brum et al, ; Jaaskelainen et al, ); or not significant (Durdiaková et al, ; Jaaskelainen, Korhonen, Voutilainen, Hippelainen, & Heinonen, ; Nowak et al, ).…”
Section: Study 3: the Relationship Between Ar(cag)n With Current Testmentioning
confidence: 92%
See 1 more Smart Citation
“…The size of the corpus callosum seems to add complexity in the relationship between spatial abilities and testosterone (Karadi et al, 2006 ). This might be one of the causes for negative findings in studies where some of the determinants are missing (Kubranska et al, 2014 ). Another cause is likely the selection of the tested population.…”
Section: Spatial Abilitiesmentioning
confidence: 99%
“…For our worked example (for study details and findings, see Table 1), we update the most recent, and largest, published meta-analysis of CAG effects on 2D:4D (Voracek, 2014), that encompassed 13 studies published up to 2014 (Butovskaya et al, 2012; De Naeyer et al, 2014; Durdiaková et al, 2013; Folland et al, 2012; Hampson & Sankar, 2012; Hurd, Vaillancourt, & Dinsdale, 2011; Knickmeyer, Woolson, Hamer, Konneker, & Gilmore, 2011; Kubranská et al, 2014; Latourelle, Elwess, & Elwess, 2008; Loehlin, Medland, & Martin, 2012; Manning et al, 2003; Mas et al, 2009; Zhang et al, 2013), which provided a maximum of 18 samples (total N = 2,909) for meta-analytic inclusion, originating from nine countries located on five continents (Australia, Belgium, Canada, China, Slovakia, Spain, Tanzania, UK, and USA). Using the same multi-pronged literature search and data retrieval strategies and the same eligibility criteria as in the previous meta-analysis (see Voracek, 2014, for details), we ascertained seven further, more recent, studies (Babková Durdiaková et al., 2017; Chang et al., 2015, Cheng, Zhao, Lu, Liu, & Liu, 2016; Durdiaková, Celec, Laznibatová, Minárik, & Ostatníková, 2016; Durdiaková et al, 2015; Warrington et al, 2018; Zhang et al, 2018), which provided 13 additional samples for inclusion, including two samples from a further country (Denmark: Chang et al, 2015).…”
Section: Methodsmentioning
confidence: 99%